Teknologi Domestikasi dan Pematangan Gonad Ikan Pawas (Osteochilus hasselti CV) dari Perairan Sungai Kampar Riau - Sukendi, Sukendi; Thamrin, Thamrin; Putra, Ridwan Manda (Universitas Riau, 2015)
A study on domestication and triggering gonadal maturation technique ofOsteochilus hasselti CV were conducted from March to May 2015. The study aimed to obtaina high quality brooder with good gonado somatic index and high quality eggs and sperm, inthat the fishes were treated with defference diets. Fish samples were kept in 1 x 1 x 1 mcages, with density of 20, 30 and 40 fishes/cage respectively. Fishes were fed on three typesof food namely dried Tubifex, shrimp pellet (without vitamin E addition) and shrimp pelletthat is enriched with vitamin E. The fishes was fed 10 % of total fish body weight/day. Itrevealed domestication can be conducted by keeping them in the cages that natural habitat.During the first week, fishes were not fed and in the following weeks they were provided withthe treated fed. The best result obtained in the fishes that are 20 fishes/cage and are feed withshrimp pellet that is enriched with vitamin E. During the research period (80 days), 20 fisheswere sampled in the 4th gonadal maturity level, their maturity indices was 14,7 %, fecundity360 eggs, egg diameter 0,936 mm and semen volume produced 0,575 ml.